Integrating Career Readiness Competencies into Vocational Curriculum for Enhanced Graduate Employability: A Case Study of Selected Trade Areas in Namibia - Sisinyize, N.; Tubaundule, G; Sihela, N; Katijere, M; Hilarious, B (International Journal of Scientific Research and Management (IJSRM), 2024)
This study explored the integration of career readiness competencies into vocational curriculum in Namibia to improve graduates' employability in key trade areas such as welding, joinery, clothing, bricklaying, hospitality, and information technology sectors. The research uses a quantitative descriptive case study method to gather data from vocational students and literature reviews. The study aims to identify the most valued career readiness competencies and assess the extent to which vocational education institutions are addressing them. The findings have implications for vocational education policy and practice, enhancing graduates' employability and economic development. It also contributes to the discussion on soft skills and career readiness in vocational education.